2012
DOI: 10.1007/s11250-012-0260-8
|View full text |Cite
|
Sign up to set email alerts
|

Oats (Avena strigosa) as winter forage for dairy cows in Vietnam: an on-farm study

Abstract: In North Vietnam, during winter, alternative forage resources are needed to balance the feed ration of dairy cows. The objective of this study was to investigate the effect of oat forage as a component of traditional winter roughage diets on feed intake, milk production and feeding cost in dairy cows. The study was conducted on-farm using 24 mid-lactation Holstein-Friesian cows. The feeding experiment consisted of two successive periods and two dietary treatments per period. Traditional basal diets included fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
2
13
2
8
Order By: Relevance
“…In the present study, CP and OM contents of Napier grass were higher than those found by other studies ( Lounglawan et al., 2014 , Mutimura et al., 2015 ). Nonetheless, Salgado et al. (2013) reported similar CP content, but higher NDF and ADF concentrations than those found in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, CP and OM contents of Napier grass were higher than those found by other studies ( Lounglawan et al., 2014 , Mutimura et al., 2015 ). Nonetheless, Salgado et al. (2013) reported similar CP content, but higher NDF and ADF concentrations than those found in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…A cultura é utilizada em sistemas de sucessão ou rotação de culturas, por apresentar menor velocidade de decomposição da palhada e liberação gradual de nutrientes, em relação a outras plantas de cobertura (CRUSCIOL et al, 2008), apresentando também elevada produção de massa verde e capacidade de proteção do solo (MARTINS et al, 2008;SOUZA et al, 2009). Ainda, de acordo com SALGADO et al (2013), a utilização de aveia preta como planta forrageira, na alimentação de vacas leiteiras, aumenta o volume de leite produzido e reduz os custos, em relação à utilização de outras dietas volumosas.…”
Section: Introductionunclassified
“…To this end, Asian countries should also consider increasing fodder production, which would decrease reliance on imported feed ingredients and also decrease cost of feeding. Lower costs of protein and energy supply from fodder/forages than from concentrates has been recorded (Salgado et al, 2012). Development of the animal industry based on locally available feed resources is expected to decrease livestock's carbon footprint and reliance on the trade.…”
Section: Feed Trade and Feed Shortage And Their Implicationsmentioning
confidence: 99%